Attraction glamor negative identity in the twentieth century - Lahoda, O.; Budiak, V. (Theory and practice of design, 2016)
The loss of established human identities and the formation of new, modified versions that appeal to the practices of everyday life in postmodern society contributed to the fact that glamour arose as a distinct identifier and the subject of research. Attitude to it as a negative trend in general, unfortunately, prevails in scientific exploration of contemporaries. However, according to the authors of the publication, the phenomenon of glamour, hedonistic lifestyle that embodies it and, definitely, a suit as a means of visual representation of glamour, have not only distinct emotional but also a significant formative potential which is not always negative. It was clearly manifested during the XX century and at the beginning of the XXI century it has become systemic manifestations in specific embodiment and operating models that provide the opportunity to not only identify but also to structure relations between the main and mediated characteristics of glamour in the context of images, fashion trends and design.